A reagent-free, sequence-dependent in situ peptide self-cyclization strategy under physiological condition - Nibedita Ghosh; Lal Mohan Kundu (Elsevier, 2024)
Cyclic peptides are an important class of bioactive molecules used as drugs as well as biomolecular probes. Peptide cyclization under the physiological environment, without added chemicals or reagents, would be a highly useful technique for in situ applications. A simple, highly efficient, and green procedure for side-chain to side-chain in situ peptide cyclization is established here at the physiological condition. The methodology further allows the release of small biologically active molecules through peptide self-cyclization. Bioactive molecules, as well as other organic leaving groups (having primary or secondary alcohol as a functional group), were conjugated to a short peptide RXE sequence (X = Pro/Ala/Gly). The peptides were designed to undergo cyclization under physiological conditions and release the covalently attached chemotherapeutic drug and nucleobases, in a controlled manner. In vitro studies were performed in detail, with optimized physiological parameters, to understand the kinetics as well as the mechanism of self-cyclization. The mechanism of action was investigated by HPLC and ESI-Mass spectrometry. The conformational change, due to cyclization of the peptides, was monitored by CD spectroscopy. The present concept of peptide self-cyclization leading to a bond cleavage could be a potential method of delivery of small, bioactive molecules such as chemotherapeutic drugs.